Learning Responding to the Religious Values of Poetry "Ketika Engkau Bersembahyang" by Emha Ainun Nadjib - Solih Hartati (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2018)
This article is intended to describe the learning respond religious value in poetry. The purpose of this study is to determine how test results and student feedback regarding religious values contained in Poetry When you pray Emha Ainun Nadjib work. This research uses descriptive method. The research objectives are students of class X-2 SMA PGRI Cianjur. Data collection techniques were used that technique tests and questionnaires. Based on the research that has been conducted on Learning Responding Value of Religious in Poetry "When you pray," Works emha ainun nadjib most students or nearly all students get good grades, and most or nearly all students provide feedback-In answer is good about values religious contained in poetry related to the value relgius faith, istiqomahan, sense of patience, gratitude, compassion, and courageous do not despair. Meanwhile, based on a questionnaire given to students of all students enjoy participating in learning the Indonesian language, and Values contained in the poem when you pray. Keywords: poetry, religious values.